Renewing Uttaranchal: Poverty to Prosperity through Bioindustrial Watershed Management - J. S. Bali (Journal of Soil and Water Conservation, 2022)
Agriculture under Indian conditions, and more so in Uttaranchal with small land holdings, would keep the poor, poor. Only when industry is mixed with agriculture, we shall see the rural youth getting skilled employment with urban wages near their homes. There would be no need to migrate, leaving only the women and old men in the villages. But the foundation of agriculture and processing industry is protection of ecology. It means forest management, biodiversity, and soil and water conservation. Only on this foundation, sustainable and balanced systems of production, based upon plants and animals, can be built. Once a balance has been restored to ecology and production systems, a stage is set for bio-industries, for value addition and profitable marketing. Infrastructure of health, education, power, roads, transport and communications, is the first necessity in the rural areas. Their neglect amounts to inflicting a disaster upon a majority of our population. The integrated implementation of all these components constitutes Bioindustrial Watershed Management. It would require massive infusion of technology and investment. Research has to combine Excellence with Relevance. Seventy per cent of our population lives in the villages. Only when rural people ‘s problems are solved and they are lifted from poverty to prosperity, shall we see India becoming a great economic power.